Governing Social Problems through Islamic Law in Aceh: A Historical-Sociological Analysis - Damanhuri Damanhuri (Jurnal Ilmiah Guru Madrasah, 2026)
Aceh has a distinctive authority to institutionalize Islamic law within Indonesia’s decentralized legal system. Although this authority is frequently associated with efforts to address social and religious offenses, its contribution cannot be assessed solely through the existence of qanun or the imposition of legal sanctions. This study examines the historical and legal foundations, institutional mechanisms, normative functions, and implementation challenges of Islamic law in governing social problems in Aceh. It employs a qualitative historical-sociological design based on documentary analysis of national legislation, Aceh qanun, institutional publications, books, and relevant scholarly articles. The documents were analyzed through qualitative content analysis and organized around four categories: historical and legal institutionalization, institutional functions, mechanisms for regulating social and religious conduct, and implementation challenges. The analysis shows that the contemporary authority of Islamic law derives from the convergence of historical legitimacy, Islamic identity, asymmetrical autonomy, national legislation, and state institutionalization. Its implementation involves a multi-actor structure comprising the Islamic Sharia Office, Wilayatul Hisbah, police, prosecutors, the Mahkamah Syar’iyah, and community and customary institutions. Islamic law also provides a shared moral framework supported by meunasah, mosques, dayah, and gampong institutions. However, limited institutional capacity, overlapping jurisdiction, uneven enforcement, insufficient legal literacy, and concerns regarding gender equality, privacy, due process, and vulnerable groups constrain its implementation. The study concludes that the contribution of Islamic law depends on accountable law enforcement, procedural justice, moral education, social protection, rehabilitation, and community participation rather than punitive enforcement alone.